β-N-methylamino-L-alanine (BMAA) suppresses cell cycle progression of non-neuronal cells - Okamoto, Saki (Sci Rep, 2018)
β-N-methylamino-L-alanine (BMAA), a natural non-proteinaceous amino acid, is a neurotoxin produced by a wide range of cyanobacteria living in various environments. BMAA is a candidate environmental risk factor for neurodegenerative diseases such as amyotrophic lateral sclerosis and Parkinson-dementia complex. Although BMAA is known to exhibit weak neuronal excitotoxicity via glutamate receptors, the underlying mechanism of toxicity has yet to be fully elucidated. To examine the glutamate receptor-independent toxicity of BMAA, we investigated the effects of BMAA in non-neuronal cell lines. BMAA potently suppressed the cell cycle progression of NIH3T3 cells at the G1/S checkpoint without inducing plasma membrane damage, apoptosis, or overproduction of reactive oxygen species, which were previously reported for neurons and neuroblastoma cells treated with BMAA. We found no evidence that activation of glutamate receptors was involved in the suppression of the G1/S transition by BMAA. Our results indicate that BMAA affects cellular functions, such as the division of non-neuronal cells, through glutamate receptor-independent mechanisms.